Consumer protection and product safety in ASEAN: a development of ASEAN general product safety directive - Al Sagoff, Syed Sagoff; Rahmah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
ASEAN Economic Community Blueprint 2025: Forging Ahead Together was endorsed by ASEAN Leaders at the 22nd ASEAN Summit in Kuala Lumpur, Malaysia. The Blueprint provides a broad framework supported by ASEAN Economic Community Council (AECC), a body entrusted with the responsibility for the implementation and monitoring of strategic measures and sectoral work plan through periodical review of key performance index. The primary purpose this body is structured as such is to have an oversight of all sectors and to use its terms of reference to direct and ensure that the synchronisation of cross-sectoral work will not only be feasible but accelerated and delivered at a pace far greater than its predecessor. Taking into account sectors that are crucial to consumer protection and product safety under the respective working group such as ASEAN Consultative Committee on Standards and Quality (ACCSQ) and ASEAN Coordinating Committee on Consumer Protection (ACCCP), it is submitted that in order to enhance consumer protection in product safety, ACCSQ and ACCCP shall develop product safety mechanism in the form of a directive or policy to overcome unsafe products in ASEAN. The finding of the research shows that there is no directive and policy in ASEAN on product safety. Therefore, the objective this research is to identify the strategy of consumer protection in product safety, to do a comparative study with European Union regarding product safety mechanism, and to propose a product safety directive in ASEAN. This research will propose ASEAN General Product Safety Directive (AGPSD) and it is hoped that the proposed AGPSD will able to help ASEAN in monitoring unsafe products.